Os efeitos do laser terapêutico (λ=830NM) em modelo experimental de osteoartrite em ratos - Oliveira, Poliani de (Universidade Federal de São Carlos, 2013)
Osteoarthritis (OA) is characterized as a chronic disease that affects synovial joints, causing degeneration and inflammation. Treatments for OA include painkillers and antiinflammatory drugs, physical exercises and, in the most serious cases, surgical interventions. Recently, can be emphasized the use of non-invasive technologies such as low level laser therapy (LLLT). In this context, the aim of this study was to evaluate the effects of LLLT on the metabolism of articular cartilage on the knees of rats in an experimental model of OA. Eighty-male rats (Wistar) were distributed into four groups: intact group (GI); injured control group (GC); injured laser treated group at 10J/cm2 (L10) and injured laser treated group at 50J/cm2 (L50). Animals were distributed into 2 subgroups, with different periods of sacrifice (5 and 8 weeks post-surgery). The anterior cruciate ligament transection (ACLT) was used to induce OA in the knee of rats. The LLLT (λ=830nm, 10 and 50J/cm2) started 2 weeks after the surgery and it was performed for 15 and 30 sessions. Qualitative and semi-quantitative histology, morphometry, immunohistochemistry and enzyme-linked immunosorbent Assay (ELISA) analysis were performed. The histological findings revealed that laser therapy modulated the progression of the degenerative process. However, laser therapy was not able of decreasing the degenerative process observed by the increased of Mankin score and cartilage thickness and it did not have any effect in the biomodulation of the expression of markers IL1β, TNF-α and MMP-13. Moreover, LLLT, at 50J/cm2 was able to increase the expression of cytokines IL-4 and IL-10. The results found in present study indicate that laser therapy 830 nm, modulate proliferation of chondrocytes in the experimental model of OA in rats but had no effect on the expression of cytokines IL-1β and TNF-α. The laser therapy 50J/cm2 LLLT was able in increasing serum expression of cytokines IL-4 and IL-10, favoring a regulatory effect of the inflammatory process.
Keywords: Lasers; Cartilagem articular; Condrócitos; Osteoartrite; Laser de baixa intensidade; Citocinas; Articular cartilage; Chondrocytes; Osteoarthritis; Laser therapy; Cytokine; OUTROS